2020
DOI: 10.1523/jneurosci.1259-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Decreases Emotional Pain Vulnerability with Associated CaMKIIα Deacetylation in Central Amygdala

Abstract: Emotional disorders are common comorbid conditions that further exacerbate the severity and chronicity of chronic pain. However, individuals show considerable vulnerability to the development of chronic pain under similar pain conditions. In this study on male rat and mouse models of chronic neuropathic pain, we identify the histone deacetylase Sirtuin 1 (SIRT1) in central amygdala as a key epigenetic regulator that controls the development of comorbid emotional disorders underlying the individual vulnerabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…However, individuals show considerable vulnerability to the development of chronic pain under similar pain conditions. In a study on male rat and mouse models of chronic neuropathic pain, it was identified SIRT1 in central amygdala is a key epigenetic regulator that controls the development of comorbid emotional disorders underlying the individual vulnerability to chronic pain (Zhou et al, 2020 ). In fact, researchers found that animals that were vulnerable to developing behaviors of anxiety and depression under the pain condition displayed reduced SIRT1 protein levels in their central amygdala, but not in those animals resistant to the emotional disorders.…”
Section: Estrogen Receptor As a Potential Example Of Biodynamic Inter...mentioning
confidence: 99%
“…However, individuals show considerable vulnerability to the development of chronic pain under similar pain conditions. In a study on male rat and mouse models of chronic neuropathic pain, it was identified SIRT1 in central amygdala is a key epigenetic regulator that controls the development of comorbid emotional disorders underlying the individual vulnerability to chronic pain (Zhou et al, 2020 ). In fact, researchers found that animals that were vulnerable to developing behaviors of anxiety and depression under the pain condition displayed reduced SIRT1 protein levels in their central amygdala, but not in those animals resistant to the emotional disorders.…”
Section: Estrogen Receptor As a Potential Example Of Biodynamic Inter...mentioning
confidence: 99%
“…SIRT1 deacetylates RelA/p65 to inhibit the nuclear translocation of NF‐κB, thus inhibiting inflammation 24 . Intrathecal injection of a lentiviral vector overexpressing SIRT1 was shown to alleviate mechanical allodynia or thermal hyperalgesia 25 . SIRT1 overexpression mediated by the lentiviral vector suppressed interleukin (IL)‐1 beta‐induced extracellular matrix degradation and cell apoptosis, alleviating the low back pain caused by intervertebral disk degeneration 24 .…”
Section: Introductionmentioning
confidence: 99%
“…24 Intrathecal injection of a lentiviral vector overexpressing SIRT1 was shown to alleviate mechanical allodynia or thermal hyperalgesia. 25 SIRT1 overexpression mediated by the lentiviral vector suppressed interleukin (IL)-1 beta-induced extracellular matrix degradation and cell apoptosis, alleviating the low back pain caused by intervertebral disk degeneration. 24 Accumulating evidence has demonstrated that enhanced synaptic plasticity of nociceptive interneurons in the spinal dorsal horn is the basis of central sensitization in neuropathic pain.…”
mentioning
confidence: 99%
“…Interestingly, the notion that H3K9 global acetylation decreases in the Schwann cells in the trigeminal ganglia of a nerve injury mouse model induced by trigeminal inflammatory compression [ 6 ], whereas that histone deacetylase inhibitors (HDACi) can prevent the persistent hypersensitivity of neurons from neuropathic pain [ 7 ], which indicate that cells in different areas of trigeminal root entry zone and ganglion contain display a different response to TN. Moreover, various HDAC subclusters have also been found to exert varying effects on pain vulnerability and excitability of neurons [ 8 , 9 ]. Therefore, the epigenetic regulation of the gene expression in response to compressive stress-induced imbalanced homeostasis in the trigeminal ganglion and trigeminal root entry zone is still obscure.…”
Section: Introductionmentioning
confidence: 99%